STUDI MINERAL AIA TIGO RASO (AIR TIGA RASA) UNTUK AIR MINUM DI NAGARI TANJUNG SANI KECAMATAN TANJUNG RAYA KABUPATEN AGAM - Sartika, Meri Dewi; Edial, Helfia; Zahara, Leni (Pendidikan Geografi, 2013)
The water is clean and healthy has to be a standard in which the consumption point is to avoid the introduction of disease from bacteria or other substances into the body that will be harmful to health. Water from Tigo Aia Raso in trust by the public has properties to cure diseases. In order to prove the efficacy of the public is willing to consume water and Aia Three Raso although quality testing as well as the minerals contained in it has never been done before. The study was descriptive using qualitative methods. To view the mineral content in Aia Raso Tigo (Three Water Sense) is pH, Fe, Na and H2S. Water in thoroughly immediately put into sterile bottles and brought to the Analytical Laboratory. The study found content of pH on the inside of the water source the Aia Tigo Raso is at 6.27 and the outside source of water is equal to 6.18. The content of iron (Fe) on the outside of the water is equal to 3.27 mg / l and to the inside of the water is 3.95 mg / l. Mineral content of Sodium (Na) on the outside of the water is equal to 107.43 mg / l and the inside of the water is equal to 106.72 mg / l. Content of Sulfide (H2S) on the outside and the water source is a small note of <0.001 mg / l.